2015
DOI: 10.1097/md.0000000000002273
|View full text |Cite
|
Sign up to set email alerts
|

Acute Acquired Concomitant Esotropia

Abstract: Acute acquired concomitant esotropia (AACE) is a rare, distinct subtype of esotropia. The purpose of this retrospective study was to describe the clinical characteristics and discuss the classification and etiology of AACE.Charts from 47 patients with AACE referred to our institute between October 2010 and November 2014 were reviewed. All participants underwent a complete medical history, ophthalmologic and orthoptic examinations, and brain and orbital imaging.Mean age at onset was 26.6 ± 12.2 years. Of the 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 15 publications
1
46
1
1
Order By: Relevance
“…Neurological diseases are considered to be associated with this type of strabismus. The morbidity was from 0 to 10% in previous studies of different sizes of samples [1, 2, 9, 11]. In the present study, only two patients presented with intracranial diseases (4.4%).…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Neurological diseases are considered to be associated with this type of strabismus. The morbidity was from 0 to 10% in previous studies of different sizes of samples [1, 2, 9, 11]. In the present study, only two patients presented with intracranial diseases (4.4%).…”
Section: Discussioncontrasting
confidence: 43%
“…In the present study, 23 out of 41 myopic patients of the Bielschowsky type wore glasses. Chen et al [9] also found that most myopic patients of the Bielschowsky type wore glasses in their study and concluded that uncorrected myopia could not be the etiology of the Bielschowsky type. Thus, whether uncorrected myopia was the etiology of this subtype of AACE was not confirmed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Inclusion criteria were: a diagnosis of AACE (deviation in all directions of gaze differing by ≤2 prism diopters (PD) when primary deviations were ≤20 PD and by ≤5 PD when primary deviations were >20 PD [ 12 ] ); no history of ophthalmic deficits or previous strabismus; no history of systemic disease or head trauma; and no neurological diseases proved by systemic neurological examinations. The patients who had a reduction in their esotropia with hypermetropic spectacle correction were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…[ 7 10 ] Recently, Kemmanu et al [ 11 ] reported a small case series of AACE in the Indian populations, in which 3 patients were found to have intracranial pathology. Chen et al [ 12 ] studied 47 Chinese patients and showed that AACE was characterized by the sudden onset of concomitant nonaccommodative esotropia with diplopia in children, and that these children had a potential for normal vision. It has been suggested that AACE might be the result of a serious neurological disease, but there is a lack of evidence to confirm this theory.…”
Section: Introductionmentioning
confidence: 99%